Design of Real-Time Demodulation for FBG Sensing Signals Based on All-Dielectric Subwavelength Gratings Edge Filters - Jingliang Lin; Ping Tang; Kaihao Chen; Jiancai Xue; Ziming Meng; Jinyun Zhou (Nanomaterials)
Accurate real-time temperature measurement under extreme thermal-pressure conditions remains challenging in aerospace. Sapphire fiber Bragg gratings (FBGs), exhibiting temperature measurement capabilities up to 1900 °C, demonstrate suitability for such extreme environments. However, the development of a high-performance demodulation system capable of processing sapphire FBG signals over wide spectral ranges at elevated speeds remains a technical challenge. This study presents a real-time FBG signal demodulation system that incorporates an all-dielectric subwavelength grating edge filter. The designed grating, comprising a TiO2/Si3N4 subwavelength unit array, modulates Mie-type electric and magnetic multipole resonances to achieve precisely tailored transmission and reflection spectra. Simulation results indicate that the grating exhibits low ohmic loss, excellent linearity, complementary transmission/reflection characteristics, a wide linear range, and angular-dependent tunability. The designed edge-filter-based demodulation system incorporates dual single-point detectors to simultaneously monitor the transmitted and reflected signals. Leveraging the functional relationship between the center wavelength of the FBG and the detected signals, this system enables high-speed, wide-range interrogation of the center wavelength, thus facilitating real-time demodulation for wide-range temperature sensing. The proposed method and system are validated through theoretical modeling, offering an innovative approach for sapphire FBG signal demodulation under extreme thermal-pressure conditions.